Distributed Leadership in School Counseling Supervision: A Qualitative Single-Case Study at a Public Senior High School - Yarmis Syukur; Netrawati Netrawati; Donal Donal (Educational Guidance and Counseling Development Journal, 2026)
This study explores the manifestation of distributed leadership within the context of guidance and counseling (GC) supervision in an Indonesian public senior high school. Despite growing recognition of distributed leadership as an effective paradigm in educational management, its application to the domain of school counseling supervision remains theoretically underdeveloped, particularly in non-Western educational settings. Employing a qualitative single-case study design, this research collected data through a semi-structured in-depth interview with one GC teacher at SMAN 8 Pekanbaru, analyzed using Braun and Clarke's thematic analysis method. Findings reveal that GC supervision is co-constructed by a network of five actors the school principal, vice-principal for student affairs, homeroom teachers, subject teachers, and the external GC supervisor each enacting distinct yet complementary supervisory functions. Five thematic clusters emerged: (1) multi-actor distribution of supervisory roles; (2) the principal's strategic and administrative supervision; (3) the external GC supervisor's clinical and professional development functions; (4) internal collaborative dynamics as an informal early-warning system; and (5) perceived gaps and developmental aspirations. The study contributes a conceptual model of distributed supervision in school counseling, demonstrates the organic emergence of distributed leadership in GC settings without formal policy design, and identifies critical implications for school policy, counselor professional development, and the regulatory framework governing GC supervision.